Combination of ONC201 and TLY012 induces selective, synergistic apoptosis in vitro and significantly delays PDAC xenograft growth in vivo. Issue 10 (2nd December 2021) - Jhaveri, Aakash V.; Zhou, Lanlan; Ralff, Marie D.; Lee, Young S.; Navaraj, Arunasalam; Carneiro, Benedito A.; Safran, Howard; Prabhu, Varun V.; Ross, Eric A.; Lee, Seulki; El-Deiry, Wafik S.
ABSTRACT: The five-year survival rate for pancreatic ductal adenocarcinoma (PDAC) has remained a dismal 9% for approximately 40 years with an urgent need for novel therapeutic interventions. ONC201 is the founding member of the imipridone class, comprised of orally bioavailable small molecules that have shown efficacy in multiple tumor types both in animal models and in Phase I/II clinical trials. ONC201 is a potent inducer of the tumor necrosis factor related apoptosis inducing ligand (TRAIL) pathway. TRAIL is an innate immune mechanism which induces programmed cell death of cancer cells. We observed that PDAC cells upregulated ATF4, CHOP, and DR5 after treatment with ONC201. This occurred in cell lines that are susceptible to ONC201-induced apoptosis and in ones that are not. In response to ONC201, PDAC cells downregulated anti-apoptotic proteins including c-FLIP, BclXL, XIAP, cIAP1, and survivin. We hypothesized that TRAIL receptor agonists might induce selective, synergistic apoptosis in pancreatic cancer cell lines treated with ONC201. We screened 7 pancreatic cancer cell lines and found synergy with ONC201 and rhTRAIL or the novel TRAIL receptor agonist TLY012 in 6 of the 7 cell lines tested. In vivo experiments using BxPC3 and HPAFII xenograft models showed that the combination of ONC201 plus TLY012 significantly delays tumor growth as compared to controls. Immunohistochemical analysis of the tumors after three doses of the combination showed significantly increased cleavage of caspase 3 in vivo as compared to controls. Taken together, the preclinical efficacy of ONC201 and TLY012 represents a novel therapeutic option for further testing in pancreatic cancer patients. This combination showed marked efficacy in tumor cells that are both sensitive and resistant to the pro-apoptotic effects of ONC201, providing rationale to further investigate the combination of ONC201 plus TLY012 in patients with pancreatic cancer.